2022
DOI: 10.1186/s12935-022-02493-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel immune-related lncRNA pair signature for prognostic prediction and immune response evaluation in gastric cancer: a bioinformatics and biological validation study

Abstract: Background Gastric cancer (GC), the most commonly diagnosed cancer worldwide with poor 5-year survival rate in advanced stages. Although immune-related and survival-related biomarkers, which typically comprise aberrantly expressed long non-coding RNAs (lncRNAs) and genes, have been identified, there are no reports of immune-related lncRNA pair (IRLP) signatures for GC. Methods In this study, we acquired lncRNA expression profiles from The Cancer Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The schematic diagram of random forests is shown in Figure 6B. In support of the finding that the polygenic risk score (PRS) model of six SNPs is capable of predicting the risk of GC, RF analyses demonstrated that the combination of the six SNPs has a high predictive power for GC, with an AUC value of 0.75, which also verifies the high fitting ability of RF (Xiaoyu Wang et al (2022) [23]). Among the current algorithms, random forests have excellent accuracy and fast training speed and can evaluate the importance of features.…”
Section: Mainstream Of Machine-learning Classification Algorithmsmentioning
confidence: 53%
See 1 more Smart Citation
“…The schematic diagram of random forests is shown in Figure 6B. In support of the finding that the polygenic risk score (PRS) model of six SNPs is capable of predicting the risk of GC, RF analyses demonstrated that the combination of the six SNPs has a high predictive power for GC, with an AUC value of 0.75, which also verifies the high fitting ability of RF (Xiaoyu Wang et al (2022) [23]). Among the current algorithms, random forests have excellent accuracy and fast training speed and can evaluate the importance of features.…”
Section: Mainstream Of Machine-learning Classification Algorithmsmentioning
confidence: 53%
“…Its mathematical expression is shown as Formula (1). Jun Wang et al (2022) [48] acquired lncRNA expression profiles from TCGA and used the LASSO to develop an immune-related lncRNA pair (IRLP) prognostic signature termed the 18-IRLP signature, which provided new insights regarding immunological biomarkers and could be used for predicting prognosis and evaluating the immune response in GC. The LASSO can be used not only for dimension reduction, but also for regression.…”
Section: Feature Selectionmentioning
confidence: 99%
“…The research methods mainly include the collection (collection and screening), processing (editing, sorting, management, and display), utilization (calculation and simulation), and analysis of biological data ( 9 , 10 ). Experience has shown that bioinformatics technology has great application value in the screening of disease biomarkers, which is of great significance for the diagnosis, treatment, and prognosis of diseases, and can provide a more comprehensive and profound understanding of diseases ( 11 - 14 ). A recent study showed that differentially expressed genes (DEGs) were significantly enriched in metabolic pathways, oxidative phosphorylation, and extracellular matrix (ECM) receptor interactions, and were closely related to fibrosis, collagen catabolic process and inflammatory response function ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al reported 23 m6A-related lncRNAs related to tumor-infiltrating immune cells, the expression of programmed death-1 (PD-1), and cytotoxic T-lymphocyteassociated protein 4 (CTLA4) [18]. Wang et al reported eighteen immune-related lncRNA pair (IRLP) signatures associated with cancer-associated fibroblasts; macrophage M2 infiltration; and PD-L1, CTLA4, LAG3 (Lymphocyte Activation Gene-3), and HLA expression in GC [19]. Wang et al reported the expression profiles of 15 m6A-related lncRNAs linked to the immune score, stromal score, and ESTIMATE score in GC [20].…”
Section: Introductionmentioning
confidence: 99%